1999
DOI: 10.1091/mbc.10.11.3825
|View full text |Cite
|
Sign up to set email alerts
|

Identification of TER94, an AAA ATPase Protein, as a Bam-dependent Component of theDrosophilaFusome

Abstract: The Drosophila fusome is a germ cell-specific organelle assembled from membrane skeletal proteins and membranous vesicles. Mutational studies that have examined inactivating alleles of fusome proteins indicate that the organelle plays central roles in germ cell differentiation. Although mutations in genes encoding skeletal fusome components prevent proper cyst formation, mutations in the bag-of-marbles gene disrupt the assembly of membranous cisternae within the fusome and block cystoblast differentiation alto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(76 citation statements)
references
References 41 publications
2
74
0
Order By: Relevance
“…From this assay, we identified a number of proteins in the Bam immunoprecipitants. In addition to the known Bam-associated partners, Ter94 (24) and eIF4A (25), observed in Bam immunoprecipitants (Fig. S1A), we also found that ubiquitin was highly enriched in Bam complexes in our assays (Fig.…”
Section: Resultssupporting
confidence: 68%
“…From this assay, we identified a number of proteins in the Bam immunoprecipitants. In addition to the known Bam-associated partners, Ter94 (24) and eIF4A (25), observed in Bam immunoprecipitants (Fig. S1A), we also found that ubiquitin was highly enriched in Bam complexes in our assays (Fig.…”
Section: Resultssupporting
confidence: 68%
“…Cul-1 has been implicated in the regulated destruction of a wide array of proteins involved in both cell cycle regulation and signal transduction (reviewed in Deshaies, 1999). Interestingly, the membrane-associated protein TER94/VSC/p97, which localizes to the fusome (Leon and McKearin, 1999), has also been implicated in ubiquitin-dependent degradation in mammals (Dai and Li, 2001). Thus, the ER component of the fusome may provide a surface for regulated protein degradation.…”
Section: Discussionmentioning
confidence: 99%
“…This was suggested by the observation that Drosophila fusome structures are enriched with the cytoplasmic protein TER94, which associates with both the Golgi complex and the ER in vertebrates (Leon and McKearin, 1999;Uchiyama et al, 2002). To characterize the structure and origin of the membranous component of the fusome, we expressed the lumenal ER-marker protein, Lys-GFP-KDEL, the resident ER membrane protein, Sec61␣-GFP, or the Golgi marker, GalTase-GFP (Cole et al, 1996), in ovarian cysts.…”
Section: The Fusome Contains Continuous Er Membranesmentioning
confidence: 99%
“…), the study of these proteins has been made easier. This is particularly true for dNSF1 (comt;Siddiqi and Benzer, 1976), TER94 (Leon and McKearin, 1999), and sed5 (Ashburner et al, 1999).…”
Section: Introductionmentioning
confidence: 99%